O uso do Discord como ferramenta de comunicação do grupo de pesquisa LA FocA - RIBEIRO, Elielson Pinto (2025)
This study investigates the effectiveness of Discord in supporting communication and the methodological implementation of research activities in the LA FocA laboratory. The theoretical foundation integrated concepts of digital communication technologies applied to collaborative research contexts. The methodology is characterized as applied research, employing a quantitative approach and content analysis procedures. Data collection was conducted directly in the laboratory environment, involving members of the LA FocA group in usability and communication experience studies with the tool. The results show that using Discord facilitates synchronous and asynchronous communication, promotes active collaboration, and enhances researcher integration. However, challenges related to the learning curve, connection stability, and limitations in data and file organization were identified as critical points impacting the full adoption of the tool.